Physicochemical Properties And Hydroxymethylfurfural (5-hmf) Content Of Kelulut Honey Processed Using Ultrasound Method - Nor Adila Zulkifli; Nurul Zaizuliana Rois Anwar; Zalilawati Mat Rashid; Zarinah Zakaria; Norshazila Shahidan; Lee-Hoon Ho; Faridah Yahya (ResearcherLinks, 2025)
Indexed by Scopus